A Biflavonoid-Rich Extract from Selaginella doederleinii Hieron. against Throat Carcinoma via Akt/Bad and IKKβ/NF-κB/COX-2 Pathways - Sisi Wang; Dingrong Wan; Wenqi Liu; Xinyi Kang; Xiuteng Zhou; Fatemeh Sefidkon; Mohaddesehossadat Mahmoud Zadeh Hosseini; Ting Zhang; Xin Pan; Xinzhou Yang (MDPI AG, 2022)
Selaginella doederleinii Hieron. is a common pharmacological plant, and this folk herbal medicine and its complex preparations have been widely used for the treatment of throat carcinoma (TC) and several associated complications in traditional Chinese medicine. This study was aimed at investigating the specific anti-throat carcinoma impacts and potential mechanisms of a biflavonoid-rich extract from S. doederleinii (SD-BFRE). The phytochemical profiling of SD-BFRE was performed by HPLC-ESI-QTOF-MS and UPLC-PDA, and the detailed pharmacological effects and mechanisms were respectively evaluated in vitro and in vivo. MTT assay, the Transwell assay and flow cytometry were performed to evaluate the abilities of SD-BFRE on inhibiting cell infiltrative growth in TC cells (Hep-2 and FaDu) in in vitro experiments. In vivo experiments used Hep-2 tumor-bearing nude mice to evaluate the anti-TC effect of SD-BFRE. Western blotting was used to explore the potential apoptotic pathway of TC cells. Here, we found that SD-BFRE exhibited anti-proliferation and pro-apoptotic effects in TC cells. Mechanistic studies have identified that SD-BFRE can suppress the activity of IKKβ and IκB-α kinase and then down-regulate the effector proteins of NF-κB/COX-2 signaling. Moreover, SD-BFRE induced apoptosis partly by regulating the Akt/Bad/caspase signaling pathway. Taken together, this study firstly demonstrated that SD-BFRE exerted its anti-TC effects by way of IKKβ/NF-κB/COX-2 and Akt/Bad pathways and might represent a potential chemotherapeutic agent for throat carcinoma.